Analyzing Number of Children Ever Born in Bangladesh Using Generalized Poisson Regression Model (Dhaka University Journal of Science, 2024)
One major indicator to detect any country’s future population size is the total fertility rate (TFR). Based on the total number of children ever born, an underdispersed count data, this paper aims to investigate the fertility behavior of mothers in Bangladesh who have given birth to one or more children. For analyzing count dataset, the Poisson regression model (PRM) is commonly used, which assumes that the response variable’s mean is equal to its variance. Since the generalized Poisson regression model (GPRM) is suitable for the analysis of both overdispersed and underdispersed count data, this model is applied to deal with the underlying count dataset in this study. The results obtained in this paper have revealed some variables that impose significant impact on the current fertility differential of mothers giving birth to children.Dhaka Univ. J. Sci. 72(2): 01-06, 2024 (July)